ANALISIS KUALITAS PUDING DENGAN PENGGUNAAN EKSTRAK WORTEL SEBAGAI PEWARNA ALAMI - Fahmi, Fithrah Iqlimia; Fridayati, Lucy; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2015)
This research was designed to analize the quality of the pudding made from carrot extract of 0% (X1), 25% (X2), 50% (X 3), 75% (X4) and 100% (X5) viewed from color, flavor, texture, and taste. This was a real experimental research which applied complete random design method and was done in three repetitions. To conduct the research, 5 experts were involved. Based on the result of the organoleptic test on the five treatments given, it was revealed that the quality of the color (orange) was in adequate category in which the highest score achieved was 3,87 on the use of 100% carrot extract. The quality of the flavor (carrot) was in adequate category in which the highest score gotten was 3,93 on the use of 100% carrot extract. The quality of the texture (soft) was in adequate category in which the highest score achieved was 3,00 on the use of 0% and 25% carrot extract. The quality of the taste (carrot) was in adequate category in which the highest score achieved was 3,80 on the use of 100% carrot extract and the taste of sweet was in adequate category in which the highest score achieved was 3,33 on the use of 25% carrot extract.Keywords : carrot extract, natural colorants, pudding, quality